2018
DOI: 10.1111/jgh.14141
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors not associated with hypomagnesemia, regardless of dose or concomitant diuretic use

Abstract: Regardless of PPI dosage or concomitant diuretics prescribed, magnesium levels were unaffected. Routine screening of serum magnesium in PPI patients appears unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Since hypomagnesemia is not readily identifiable on regular blood testing, many patients might develop this condition unknowingly. In contrast, data of 2400 patients were retrospectively inspected by Chowdhry et al and they did not find significant differences between the PPI users and non-users [88]. The lack of significance persisted even after considering the dose of PPI and concomitant use of diuretics [88].…”
Section: Mechanism Of Bone Fractures Induced By Ppimentioning
confidence: 99%
See 1 more Smart Citation
“…Since hypomagnesemia is not readily identifiable on regular blood testing, many patients might develop this condition unknowingly. In contrast, data of 2400 patients were retrospectively inspected by Chowdhry et al and they did not find significant differences between the PPI users and non-users [88]. The lack of significance persisted even after considering the dose of PPI and concomitant use of diuretics [88].…”
Section: Mechanism Of Bone Fractures Induced By Ppimentioning
confidence: 99%
“…In contrast, data of 2400 patients were retrospectively inspected by Chowdhry et al and they did not find significant differences between the PPI users and non-users [88]. The lack of significance persisted even after considering the dose of PPI and concomitant use of diuretics [88]. This was confirmed by another prospective study, whereby PPI treatment for 12 months did not lower serum magnesium level significantly among patients ( n = 209) [89].…”
Section: Mechanism Of Bone Fractures Induced By Ppimentioning
confidence: 99%
“…The characteristics of identified studies were presented in Table 1. [10,1326] A total of 15 studies involving 129,347 participants, with sample sizes varying from 52 to 95,205 were included in the present review. The first authors were from the United States of America (7/15, 46.7%), the Netherland (1/15, 6.7%), Switzerland (1/15, 6.7%), Japan (1/15, 6.7%), Korea (1/15, 6.7%), Belgium (1/15, 6.7%), Brazil (1/15, 6.7%), Croatia (1/15, 6.7%), and Israe (1/15, 6.7%).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, previous observational studies have indicated that the risk of hypomagnesemia is associated with the use of PPIs, but the results were controversial. For example, Chowdhry et al [10] investigated the clinically significant alteration of serum magnesium levels in 2400 patients treated with various PPIs at different dosages, with or without diuretics. The results revealed that mean magnesium levels remained unchanged in patients treated with PPIs ( P =.40), and there was no statistical difference in the prevalence of hypomagnesemia (14.7% vs 15.1%, P =.77).…”
Section: Introductionmentioning
confidence: 99%
“…Analogously, no significant differences between subjects in cure with PPIs at variable doses, with or without associated diuretics, and the control group were observed. On this base, previous studies on hypomagnesemia and PPI use should be reconsidered with caution [ 44 ]. No data are available at the best of our knowledge, regarding magnesium status in pregnant women undergoing PPI use.…”
Section: Mg Interactions With Proton Pump Inhibitor Medicationsmentioning
confidence: 99%